Fundamental Rights in Times of Emergency: Ataur Rahman vs Muhibur Rahman Revisited - Rahman, Md Mustakimur (Faculty of Law, Universitas Brawijaya, 2018)
This research analyses the Bangladesh's Court Decision on the case of Ataur Rahman vs. Mahibur Rahman with regrad to fundamental rights in times of emergency. It is argued that the decision of the court in Ataur Rahman vs. Muhibur Rahman is erroneous decision. This is because while Article 141C of Bangladesh Constitution gives the Presidnet the power to suspend certain fundamental rights, yet Articles 27 to 35 and 41 of the Constitution cannot be suspended. In Bangladesh's legal system, fundamental human rights are commonly viewed as a set of legal protections. Part III of the Constitution of Bangladesh has confirmed these rights for the citizens of Bangladesh. Some fundamental rights are even universally recognized rights which are contained in the United Nations Universal Declaration of Human Rights (UDHR), the UN International Covenant on Civil and Political Rights (ICCPR), or the UN International Covenant on Economic, Social and Cultural Rights (ICESCR). Article 4 of the ICCPR deals with the state of emergency and Article 4(2) provides a list of non-derogable rights. Such as the right to life, the prohibition of torture, slavery etc. These rights are completely non-derogable in nature and cannot be derogated at all including during a state of emergency. Furthermore the Apex court of Bangladesh tried to justify that the President can derogate any fundamental right during an emergency. Such a proposition is contradicting core parts of our Constitution as well as several international instruments. This research uses normative legal research with statute approach and case approach, especialy analysing Ataur Rahman vs. Muhibur Rahman case.